2017
DOI: 10.1002/ppul.23912
|View full text |Cite
|
Sign up to set email alerts
|

Regional lung function testing in children using electrical impedance tomography

Abstract: Global and regional lung functions were not affected by exercise in lung-healthy children. Exercise did not increase ventilation inhomogeneity. The obtained EIT-derived regional lung parameters can serve as reference values for future studies in children with lung diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(86 reference statements)
1
10
0
2
Order By: Relevance
“…Nonsmokers The time-dependent functional information from PFT can be visualised by means of the regional lung function parameters t50, t75 and t90. This allows not only the detection of differences in ventilation distribution among several study groups, as shown in our current study, but also timely changes in ventilation distribution between two measuring times in one individual such as before and after exercise challenge or before and after administration of bronchodilators as already shown in small studies [10][11][12]. In one of the first studies on PFT and EIT we detected differences in spatial and temporal ventilation distribution between lung-healthy subjects and patients with COPD [6].…”
Section: Smokerssupporting
confidence: 80%
See 2 more Smart Citations
“…Nonsmokers The time-dependent functional information from PFT can be visualised by means of the regional lung function parameters t50, t75 and t90. This allows not only the detection of differences in ventilation distribution among several study groups, as shown in our current study, but also timely changes in ventilation distribution between two measuring times in one individual such as before and after exercise challenge or before and after administration of bronchodilators as already shown in small studies [10][11][12]. In one of the first studies on PFT and EIT we detected differences in spatial and temporal ventilation distribution between lung-healthy subjects and patients with COPD [6].…”
Section: Smokerssupporting
confidence: 80%
“…Despite smaller scan rates than conventional PFT dominated by spirometry and plethysmography, EIT delivered data at a scan rate of 33 images per second in the present study, in up to 836 regional values of a certain regional lung function parameter, such as FEV1,EIT in the examined thorax cross section. Conventional PFT provides only one value, such as global FEV1 measured at the airway opening [10,24].…”
Section: Exsmokersmentioning
confidence: 99%
See 1 more Smart Citation
“…The core patient population that might benefit from chest EIT are critically ill patients treated in neonatal (Chatziioannidis et al, 2013;Miedema et al, 2013;Rossi et al, 2013;Hough et al, 2014;van der Burg et al, 2016) and paediatric intensive care units (Steinmann et al, 2013;Wilsterman et al, 2016;Lupton-Smith et al, 2017). Children suffering from chronic lung diseases like cystic fibrosis or asthma (Lehmann et al, 2016;Mueller et al, 2018;Ngo et al, 2018;Vogt et al, 2018;Roethlisberger et al, 2018), especially those in the preschool age that cannot reliably perform conventional forced spirometric pulmonary function tests, represent another large patient group where EIT might become clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…EIT has mainly been used in adult patients in the intensive care unit, but more recently investigators have applied EIT to the study of pediatric respiratory disease. Vogt et al assessed regional lung ventilation using EIT in healthy children at baseline and after an exercise challenge. They obtained spirometry and EIT data from 90 healthy children ages 3 to 16 years, and they compared their results to data from 3 patients with CF.…”
Section: Introductionmentioning
confidence: 99%